A proposed protocol of medical negligence on-board International Common Carrier Flights in the context of international law treaties and/or Instruments - Carstens, Pieter Albert, 1960- (University of Pretoria, 2017)
Mini Dissertation (MPhil)--University of Pretoria, 2017.